Cultured reindeer, domesticated land, and (self)-cultivated herders: Histories and structures of reindeer herding landscapes in the European part of Russia - Kirill V. Istomin (Pastoralism, 2023)
Abstract This paper attempts to analyse diverse forms of reindeer pastoralism that exist in the European part of Russia from the viewpoint of landscape approach, that is as unique localized and historically developed interaction between people, reindeer and the natural landscape. The analysis starts with a short overview of the history of reindeer herding in the two reindeer herding regions of European Russia: the Archangelsk tundras and the Kola Peninsula. The developments of the last 300 years related to the transition from pre-pastoralist reindeer herding to reindeer pastoralism and the development of reindeer pastoralism during the late Imperial and Soviet periods are shown as particularly important. During this period, the particular form of reindeer-animal interaction developed in the Archangelsk tundras and characterized by intensive control over the herds and long linear interzonal migrations became dominant throughout European Russia before disintegrating again into a set of more localized forms by the late Soviet to early Post-Soviet periods. The discussion proceeds by analysing interactions between herders, reindeer and environment in the two main forms of reindeer pastoralism present in European Russia now in the most part of the Kola Peninsula and the most part of the Archangelsk tundras respectively. It is demonstrated that these two forms essentially depend on the interactions between reindeer, people and environment that existed in previous periods and have left traces in the physical landscape as well as in reindeer behaviour. The current modes of interaction between the elements of reindeer landscape build on them in different ways. Besides the two main forms, there are three small localities in European Russia where other forms of landscape interactions can be found.